1991
DOI: 10.1016/0378-1097(91)90389-r
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of non-β-lactamase-mediated ampicilin-resistant Haemophilus influenzae

Abstract: We questioned whether strains of ampicillin-resistant, non-beta-lactamase-producing (AmpR NBLP) Haemophilus influenzae with lower affinity penicillin-binding proteins (PBPs) might have altered virulence. The virulence of resistant transformant strains and the susceptible recipient was compared using infant rats. Following intraperitoneal inoculation, there was a significantly lower mortality rate and incidence and magnitude of bacteremia with two of three transformants compared to the recipient strain. Reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Rubin et al [21] have suggested that such strains are less virulent than strains without alterations in PBPs, which might explain the low prevalence observed in most studies. While the role in therapeutic failure of such resistant strains has not been clear, ampicillin treatment failed in a patient with meningitis and endocarditis due to a BLNAR strain (ampicillin MIC of 6.25 Ìg/ml) [22].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Rubin et al [21] have suggested that such strains are less virulent than strains without alterations in PBPs, which might explain the low prevalence observed in most studies. While the role in therapeutic failure of such resistant strains has not been clear, ampicillin treatment failed in a patient with meningitis and endocarditis due to a BLNAR strain (ampicillin MIC of 6.25 Ìg/ml) [22].…”
Section: Discussionmentioning
confidence: 72%
“…All ß-lactamase-producing strains thus were ampicillin resistant (ampicillin MICs of 14 Ìg/ml). Although 35 ß-lactamase-negative strains were ampicillin-susceptible (MICs, &0.5 Ìg/ml), 28 ß-lactamase-negative strains (44.4% of all ß-lactamase-negative isolates) Chemotherapy 1999;45: [15][16][17][18][19][20][21] Seki/Kasahara/Ohta/Ohta/Saikawa/ Sumita/Yachie/Fujita/Koizumi …”
Section: Patient Characteristicsmentioning
confidence: 99%
“…This is in agreement with numerous previous surveillance studies, which have indicated that such observations remain uncommon (11,13,14). It has been postulated that BLNAR is associated with altered penicillin-binding proteins (PBPs) and might be due to a lower virulence of strains with abnormal PBPs (13,16,26).…”
Section: Discussionmentioning
confidence: 99%
“…Another suggested reason for the limited clinical impact of H. influenzae with altered PBPs has been its virulence. Rubin et al (28) have shown in the infant rat model of bacteremia that the relationship between resistance and virulence in these , purulent effusion behind pars tensa and pars flaccida; o and p, purulent effusion behind pars flaccida;^and _, clear to slightly turbid effusion; ᮀ, no changes. NA, not applicable.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the virulence of these strains are sparse, but it has been suggested that they may have a lower virulence potential. In the infant rat model of bacteremia, a reduced mortality and a reduced magnitude of bacteremia were observed after intraperitoneal inoculation of ampicillin-resistant transformant, nontypeable H. influenzae strains (28). However, both the site of infection and the in vivo proliferation were questioned.…”
mentioning
confidence: 99%